Средний класс, демократические ценности и политические предпочтения: до и после "оранжевой революции" - Колодий, И. (Социология: теория, методы, маркетинг, 2007)
The western political science is traditionally characterized by the research direction(Almond, Verba, Inkles, Inglehart) that believes in the existence of political culture promoting a model of representative democracy. This kind of political culture contains views and values, which support an existing democratic system and encourage democratization of autocracies. However, there is another research direction (De Graaf,Werfhorst, Güveli) emphasizing a special role of the new middle class members who adhere to democratic views and prefer to vote for the parties belonging to the left wing of political spectrum. If these statements are true, so, possibly, the class factor and the factor of pro-democratic political culture should play an essential role in the internal political situation. The paper is aimed at accomplishing the attempt to analyze the connection between political culture, class and voting preferences in Ukraine.